2006
DOI: 10.1007/s00122-005-0182-1
|View full text |Cite
|
Sign up to set email alerts
|

Unigene derived microsatellite markers for the cereal genomes

Abstract: Unigene derived microsatellite (UGMS) markers have the advantage of assaying variation in the expressed component of the genome with unique identity and positions. We characterized the microsatellite motifs present in the unigenes of five cereal species namely, rice, wheat, maize, Sorghum and barley and compared with those in Arabidopsis. The overall UGMS frequency in the five cereal species was 1/7.6 kb. The maximum UGMS frequency was in rice (1/3.6 kb) and the lowest in wheat (1/10.6 kb). GC-rich trinucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
77
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 27 publications
13
77
1
2
Order By: Relevance
“…The amino acids serine, leucine, glutamine, and phenylalanine were predominant. Similar predominance of these amino acids has also been reported in other plant species (Jung et al 2005;Lawson et al 2006;Parida et al 2006;Roorkiwal and Sharma 2011).…”
Section: Microsatelites In Coding Regionssupporting
confidence: 83%
“…The amino acids serine, leucine, glutamine, and phenylalanine were predominant. Similar predominance of these amino acids has also been reported in other plant species (Jung et al 2005;Lawson et al 2006;Parida et al 2006;Roorkiwal and Sharma 2011).…”
Section: Microsatelites In Coding Regionssupporting
confidence: 83%
“…Our findings confirm and expand the results of previous studies indicating the high transferability of COS markers between species (Parida et al 2006;Burt and nicholson 2011;Howard et al 2011;Molnár et al 2013). The fact that 64.2 % of the products obtained with chromosomes isolated from wild relatives were polymorphic relative to those obtained in hexaploid wheat suggested that the substantial genetic diversity of wild progenitors is due to the variability of intron regions (Yu et al 2005).…”
Section: Discussionsupporting
confidence: 90%
“…UGMS markers have been recently developed in order to use unique functional genes in the plant genomes as molecular markers (Parida et al 2006(Parida et al , 2010. This has reduced the redundancy, i.e., multiple copies of genes or repeats of the same DNA sequences, which is a general problem when SSRs are designed from random genomic DNA or EST sequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the problem of sequence redundancy yielding multiple sets of markers at the same locus, random EST sequences are being assembled into unique gene sequences called unigenes (http://www. ncbi.nlm.nih.gov/), and SSRs are designed from these transcribed genes in order to have unique identities and positions in the genome (Parida et al 2006, Sharma et al 2009). The availability of increasingly large unigene databases now makes systematical and easy identification of microsatellites from a large number of plants possible, greatly facilitating the study of functional diversity in the natural populations and many germplasm collections as well as comparative mapping and evolutionary studies (Ishikawa et al 2008, Parida et al 2006.…”
Section: Introductionmentioning
confidence: 99%